2010
DOI: 10.1111/j.1745-4557.2010.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Antioxidants on Irradiated Beef Color

Abstract: Fresh beef was dipped into ascorbic acid (AA; 500 ppm), butylated hydroxyanisole (BHA, 150 ppm), butylated hydroxytoluene (BHT, 100 ppm) or propyl gallate (PG; 100 ppm); control samples were dipped in deionized water. Samples were vacuum packaged, then irradiated (0, 1.25 or 2.50 kGy). After irradiation, samples were stored (0, 7 or 14 days) at 4C. Color was assessed instrumentally (L*, a*, b*values, hue angles, chroma) and visually. All antioxidants increased L*value by two units (lighter); however, irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
1
0
1
Order By: Relevance
“…This study found that goat milk showed slight browning after electron beam irradiation, suggesting that the color of the milk may be affected by the treatment. Furthermore, radiation‐induced hydroxyl radicals or other reactive oxygen species (ROS) can oxidize lipids and other reducing compounds in food 18 . The most significant change in color was observed in pasteurized milk, which showed a significant overall color difference Δ E * compared to the control group, as demonstrated in the representative data.…”
Section: Resultsmentioning
confidence: 87%
“…This study found that goat milk showed slight browning after electron beam irradiation, suggesting that the color of the milk may be affected by the treatment. Furthermore, radiation‐induced hydroxyl radicals or other reactive oxygen species (ROS) can oxidize lipids and other reducing compounds in food 18 . The most significant change in color was observed in pasteurized milk, which showed a significant overall color difference Δ E * compared to the control group, as demonstrated in the representative data.…”
Section: Resultsmentioning
confidence: 87%
“…A irradiação significativamente aumenta os valores de TBARS em produtos ricos em lipídios sobre diferentes condições de estocagem, condições de processamento e tipos de embalagem (DU et al, 2000;GOMES et al, 2002;HENRY et al, 2010;LOVE;AHN, 2003;PARK et al, 2010;RABABAH et al, 2006;RAMAMOORTHI et al, 2010;MANCINI-FILHO;VILLAVICENCIO, 2009VILLAVICENCIO, , 2010YILDIRIM;UZUNLU;TOPUZ, 2005).…”
Section: Irradiação De Alimentosunclassified